2018
DOI: 10.1111/ene.13582
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous thrombolysis for acute ischaemic stroke in patients on direct oral anticoagulants

Abstract: In this expert opinion paper, it is suggested that IVT can be performed in patients selected according to the time elapsed since the drug was last taken, renal function, type of hospital where the patient is admitted and plasma concentration of DOAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 69 publications
(56 reference statements)
0
57
0
Order By: Relevance
“…[5][6][7] While an INR cut-off value of ≤1.7 is widely accepted for thrombolysis in warfarinised patient based on data from observational studies, there is no such data for DOAC treated patients. [5][6][7] While an INR cut-off value of ≤1.7 is widely accepted for thrombolysis in warfarinised patient based on data from observational studies, there is no such data for DOAC treated patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] While an INR cut-off value of ≤1.7 is widely accepted for thrombolysis in warfarinised patient based on data from observational studies, there is no such data for DOAC treated patients. [5][6][7] While an INR cut-off value of ≤1.7 is widely accepted for thrombolysis in warfarinised patient based on data from observational studies, there is no such data for DOAC treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Current experience of intravenous thrombolysis in DOAC patients is mostly limited to using antidote on spec or instigating treatment without DOAC specific testing in the majority of patients. [5][6][7] While an INR cut-off value of ≤1.7 is widely accepted for thrombolysis in warfarinised patient based on data from observational studies, there is no such data for DOAC treated patients. Except in Australia, international stroke guidelines do not include any suggested DOAC drug cut-off levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is expected to be improved in similar cases. In a Franch retrospective research, patients with acute ischemic stroke who were treated with dabigatran within 48 hours were recommended for intravenous thrombolysis after idarucizumab's reversal without direct prothrombin activity monitoring [9] .Giannandrea [10] reviewed 55 thrombolytic cases after idarucizumab reversal of dabigatran showed that 81.9% (45 cases) of patients had improved NIHSS score (median 5 points). In a retrospective study of 120 patients with acute ischemic/hemorrhagic stroke in Germany, the e cacy and safety of idarucizumab reversal of dabigatran in intravenous thrombolysis with acute ischemic stroke had been con rmed.However, in patients with hemorrhagic stroke, the application of can prevent the expansion of hematoma and improve the prognosis of patients [11] .…”
Section: Discussionmentioning
confidence: 99%
“…The improved accuracy at lower dabigatran concentration is most likely secondary to calibration methods, as ECA‐T calibration used 3‐4 points (0 [optional], 30, 255, and 468 ng/mL) and ECA‐II had a fivepoint calibration curve (0, 52, 106, 182, and 270 ng/mL). These data, coupled with the protocol changes (Table 1) would suggest that protocol modifications are required to cover the entire testing range, but no change may be necessary if accuracy is more clinically relevant at lower dabigatran concentrations (<50 ng/mL) for cases of emergent interventions 43,44 . In addition, the methodology of Diagnostica Stago for the ECA‐II assay uses reflex testing meaning that, when the concentration is above the higher calibration point, an automatic re‐dilution of the samples is performed by the analyzer (from 1/5 in the initial analysis to 1/15 in the re‐diluted analysis, increasing the potential range of measurement until 750 ng/mL approximatively).…”
Section: The Ecarin Chromogenic Assaymentioning
confidence: 99%